1986
DOI: 10.2134/agronj1986.00021962007800020021x
|View full text |Cite
|
Sign up to set email alerts
|

Copper Deficiency in Cereal and Oilseed Crops in Northern Canadian Prairie Soils1

Abstract: Transitional grassland/forest light soils in Saskatchewan are often deficient in Cu. The high cost of micronutrient fertilizers necessitates extreme care in identifying micronutrient deficiencies and selecting effective products and methods of application. Comparison of tissue and grain or seed analysis for spring wheat (Triticum ustivum L.), canola (Brassica napus L.), and flax (Linum usitatissimum L.) vs. DTPA-extractable soil Cu levels revealed that diagnosis of Cu deficiencies can more accurately be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
0
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 5 publications
5
40
0
2
Order By: Relevance
“…This suggests that dispersion and availability of Cu from the granules, especially from large granules , may be a major problem on farm fields. This also suggests that the lack of dispersion of Cu ions from granular Cu fertilizers and subsequently reduced Cu availability to crop plants can be overcome by application in the previous autumn (Karamanos et al 1986;Malhi et al 1989Malhi et al , 2005.…”
Section: Seed Yield and Cu Uptakementioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that dispersion and availability of Cu from the granules, especially from large granules , may be a major problem on farm fields. This also suggests that the lack of dispersion of Cu ions from granular Cu fertilizers and subsequently reduced Cu availability to crop plants can be overcome by application in the previous autumn (Karamanos et al 1986;Malhi et al 1989Malhi et al , 2005.…”
Section: Seed Yield and Cu Uptakementioning
confidence: 99%
“…Previous field experiments on corn in Egypt have also indicated that use of corn seeds soaked in Zn, Mn and Fe solution could enhance NFUE leading to improvement in seed yield and N recovery (Teama 2001). However, it must be remembered that soil-applied Cu fertilizers at relatively high rates should have much longer-term residual effects on crop yield compared with foliar or seed-soaked Cu fertilizer treatments applied at low Cu rates (Gartrell 1980;Malhi et al 1989;Solberg et al 1996;Karamanos et al 1986Karamanos et al , 2005.…”
Section: Seed Yield and Cu Uptakementioning
confidence: 99%
See 3 more Smart Citations